Ekspansi Desa dan Implikasinya Terhadap Kehidupan Sosial Budaya Masyarakat: (Studi Pada Masyarakat 'Kundi Bersatu' Kecamatan Simpang Teritip Kabupaten Bangka) - Rezi Prayoga (Society, 2017)
Village Expansion and Its Implication towords Socio-Cultural Life of the Society ( A Study at ‘Kundi Bersatu’ Society Simpang Teritip Sub-District West Bangka Regency). (Supervised by Ibrahim and Jamilah Cholillah). Village expansion is one of a series of regional autonomy processes to create some areas into section so that the process of governance can work effectively and efficiently. The implementation of village expansion makes the separation of society life into three administrative regions. This research aims to analyze and identify village expansion and its implication towords socio-cultural life of the society. The theory used to analyze village expansion and its implication towords socio-cultural life of the society is theory social capital by James Coleman about relationship structure and network. Social capital is a relationship and network to tie individual relationships within a society. In other words, these relationship structure and network facilitate actor or people to be able to work together to achieve certain interests. The type and approach in this research were descriptive qualitative research using data collecting technique in the form of direct observation, unstructured interview, and documentation. Based on the field research that shows the implementation of village expansion that happens on the society of ‘Kundi Bersatu’ does not have significant impact on socio-cultural life of the society. It is seen from the condition of society life before and after village expansion, where social conditions of society tend not to change, so that society life still united. It is seen from the strenght of social solidarity of the society and the custom still preserved well after village expansion. There are some factors that influence the implication of village expansion in socio cultural society life consisted of internal factor including custom factor, religion, and kinship ties. External factor consisted of geographical factor and natural resources as joint assets.